Optimization of Different Stocking Densities on Growth and Survival Rate of Bonylip Barb (Osteochilus vittatus) Larvae - Yeni Ika puji Astuti; waluyo Waluyo; Shobrina Silmi Qori Tartila (Universitas Teuku Umar, 2026)
This study aimed to determine the optimal stocking density on growth and survival rate of bonylip barb larvae. This study applied a completely random design experimental method with three treatments, namely 5 fish/L, 15 fish/L and 25 fish/L, in triplicates. Parameters obtained were composed of weight gain (WG), length gain (LG), survival rate (SR), and feed intake (FI). All data were analyzed using an analysis of variance (ANOVA) to determine the significance condition. If there were any significant difference on the data, a further analysis was conducted using the DMRT (Duncan’s Multiple Range Test). The results showed that the optimal stocking density for bonylip barb fish larvae is 5 fish/L, due to showing the best treatment on WG, SR, and FI (p<0.05), although having no significant difference in LG among different treatments (p>0.05). This study concludes that different stocking densities can affect the growth and survival of bonylip barb larvae, with the best results observed at a density of 5 fish/L.